Beneficial effect of ABO incompatibility on de novo DSA production after kidney transplantation. (July 2018) - Kobayashi, Takaaki; Okada, Manabu; Iwasaki, Kenta; Horimi, Kosei; Matsuoka, Yutaka; Miwa, Yuko; Uchida, Kazuharu; Takeda, Asami; Goto, Norihiko; Narumi, Shunji; Watarai, Yoshihiko
Abstract : Introduction: De novo donor specific HLA antibodies (DSA)-induced chronic antibody-mediated rejection (ABMR) is one of major obstacles to long term graft survival. Recently, ABO incompatible kidney transplantation (ABO-I) has showed favorable graft survival. We have reported that anti-A/B antibody binding could cause graft accommodation, which demonstrated protective effects against graft injury due to upregulation of complement regulatory proteins (CD55/CD59) and downregulation of HLA class II antigens. The purpose of this study was to elucidate the effect of ABO incompatibility on de novo DSA production after kidney transplantation. Methods: HLA-DRB1/3/4/5 and DQB1 epitope mismatch (MM) levels and de novo DSA production were examined in 681 living donor kidney transplantations [449 ABO-identical/compatible (ABO-Id/C), 232 ABO-I] performed between 2008 and 2015. Desensitization in ABO-I included rituximab (RIT, n=164), splenectomy (SPX, n=10) and neither (NONE, n=58) due to low anti-A/B antibody titers. Results: De novo DSA were detected in 80 recipients (11.7%) including DSA against class I (n=9), class I+DQ (n=2), DR (n=14), DQ (n=50) and DR+DQ (n=5). Biopsy-proven chronic ABMR was significantly associated with DR DSA (HR 14.7, P=0.0003) and DQ DSA (HR 33.1, P<0.0001), but not class I DSA. Therefore, only class II (DR and/or DQ) DSA were considered in this study. Epitope MM levels of DRB1/3/4/5 and DQB1 were significantly correlated with production of DR and DQ DSA, respectively (Fig. 1). De novo DSA free graft survivals with moderate MM levels (6-15 DRB1/3/4/5 MM and 1-5 DQB1 MM) were significantly higher in ABO-I (DR 100%, DQ 100%) than in ABO-Id/C (DR 96.3% P=0.0378, DQ 90.7% P=0.0143) (Fig. 2). ABO-I without rituximab pretreatment also exhibited the favorable results for de novo DSA production (Fig. 3).. Figure. No caption available. Figure. No caption available. Figure. No caption available. Conclusions: DRB1/3/4/5 and DQB1 epitope MM levels could predict the risk of de novo DSA production. Protective effect against de novo DSA production was observed in ABO-I with moderate levels of DRB and DQB epitope MM. Beneficial effect of ABO incompatibility may be elicited by anti-A/B antibody binding to the graft, rather than rituximab pretreatment.